Jump height analysis on tennis serve - Dossena, F.; Rossi, C.; La Torre, A.; Bonato, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Tennis serve has become one of the most important shots in modern tennis, allowing players to gain points with no or very short rallies. In order to gain maximal speed during tennis serve the contribution of both upper and lower limbs is necessary. In particular, lower limbs generates about 50% of the total force developed during the serve. On the other hand, limited information are available about lower limbs activity during tennis serve. Therefore, the aim of this study was to investigate possible relationship between the jump height and anthropometric characteristics during serve performance. Methods: Eight professional tennis players, 4 elite (300-800 of ATP official ranking) and 4 professional tennis players (age 19±4 y-o; height 181±3 cm; height with racket 283±5 cm) participated in the study. Players performed five first and 5 second balls and five first and 5 seconds serving on a 10 cm wood platform directly in the tennis court. Jump height during tennis serve was measured with a high-speed camera. Serve speed was measured with a radar apparatus placed 2 meters behind the player on the ideal serve trajectory axis. Serve efficacy was evaluated hitting a target zone in the middle of the serve area. In addition, three series of counter movement jump (CMJ) and counter movement jump free (CMJF) with high-speed camera to evaluate jump height were measured. Results: Pearson correlation analysis showed a positive relationship between players height and jump height during the first serve (R=0.8; P=0.03). Unpaired t-test revealed that using both CMJ and CMJF elite tennis players used an high percentage of jump during the first (CMJ: 37±4 % elite vs 27±8 % professional, p=0.02; CMJF: 31±2% elite vs 22±5% professional, p=0.004), and second ball (CMJ: 38±5% elite vs 29±5% professional, p=0.0003; CMJF: 31±4% elite vs 24±4% professional, p=0.0001) of the serve. Moreover, during the second serve elite tennis players reached a higher jump height compared to professionals (13.6 ± 2.2 cm, elite vs 10.7 ± 2.3 cm professional, p=0.001). No significant difference in ball speed and efficacy between elite and professionals were detected. When serving on the wooden platform, elite players had a better efficacy in the first serve respect to professional players (p=0.028). Also in this situation no significant differences in ball speed between elite and professionals were founded. Discussion: Reaching higher jump heights during tennis serve seems not to be effective both in the first both in the second ball. In addition, an acute improvement of height for serving was not an effective solution for improving ball speed and serve efficacy. This because, serve performance requires the coordinate action of several body segments to produce optimal racquet position, trajectory and velocity at ball impact. In conclusion, coaches of top-level athlete have to insist on serve technique rather than jump height.